A kind of iron phosphide active material and its preparation method and application

By using the baked iron phosphide active material in lithium oxygen batteries and composited with nitrogen doped carbon nanotubes, the problem of poor performance of discharge products accumulation and recovery materials in lithium oxygen batteries is solved, and the effect of improving the number of battery cycles and charging and discharging utilization is achieved.

CN118771325BActive Publication Date: 2025-03-14YANTAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410766408.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-03-14
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

In practical applications, lithium oxygen batteries have problems such as poor conductivity, reduced reaction kinetics and shortened cycle life, and the existing methods of recycling cathode materials have problems such as large energy consumption, high cost and poor material performance.

Method used

Iron phosphate active material is prepared by placing the decommissioned lithium iron phosphate positive electrode material on melamine under a protective atmosphere, and a catalyst with a multi-stage pore structure is formed by calcining.

Benefits of technology

The reactive site of the positive electrode material of the lithium oxygen battery is improved, the material utilization rate is improved, the storage capacity of the discharge product lithium peroxide is enhanced, and the number of cycles and charge and discharge utilization rate of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771325B_ABST
    Figure CN118771325B_ABST
Patent Text Reader

Abstract

The present invention discloses an iron phosphide active material and a preparation method and application thereof, comprising the following steps: placing a retired lithium iron phosphate positive electrode material on top of melamine under an inert atmosphere, and obtaining the iron phosphide active material after roasting. The present invention prepares the retired lithium iron phosphate battery positive electrode material into an iron phosphide active material by a one-step in-situ thermal conversion method. At the same time, by utilizing the catalytic effect of the transition metal iron element, carbon nanotubes grow on the surface of the iron phosphide active material, thereby obtaining a high pore utilization rate and connectivity, and obtaining an iron phosphide active material with a three-dimensional structure having a high specific surface area. The iron phosphide active material is used to prepare the positive electrode material of a lithium oxygen battery, providing more reactive sites for the electrochemical reaction, improving the material utilization rate, and facilitating the storage of the discharge product lithium peroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium oxygen batteries, and in particular to an iron phosphide active material and a preparation method and application thereof. Background Art

[0002] The actual positive electrode of lithium oxygen battery is oxygen in the air, and its theoretical energy density can reach 11430Wh kg -1 Therefore, in recent years, it has been regarded as the next generation of ideal energy storage device due to its unique semi-open structure and extremely high theoretical energy density. However, there are still certain challenges in practical application. The main reasons are: the accumulation of discharge products on the positive electrode surface leads to poor conductivity, reduces reaction kinetics, and shortens cycle life.

[0003] Developing materials with high catalytic activity and reasonable pore structure design is the key to solving the problem. A series of non-precious metal-based materials, such as metal oxides, metal sulfides, metal nitrides and metal carbides, have also been widely studied as positive electrodes for lithium-oxygen batteries.

[0004] In recent years, waste lithium-ion batteries have received extensive attention. The mainstream positive electrode materials in LIBs are lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium cobalt oxide. Among them, the positive electrode material of lithium iron phosphate batteries accounts for about 40% of the battery production cost and has a high recycling value. Among them, transition metals and their derivative materials also have certain activity in inducing the growth of discharge products Li2O2 and catalyzing the formation and decomposition of Li2O2. In addition, by adjusting the pore structure of non-precious metal-based catalysts, high-performance lithium oxygen battery positive electrodes with efficient mass transfer channels and large Li2O2 storage space can also be prepared.

[0005] At present, there are three methods for recycling positive electrode materials: pyrometallurgy, hydrometallurgy and direct recycling. However, pyrometallurgy requires high-temperature smelting, which consumes a lot of energy and causes secondary pollution; hydrometallurgical technology requires the use of a large amount of acid and alkali reagents, which not only produces wastewater, but also greatly increases costs; in direct recycling technology, although the material phase can be restored, its electrochemical performance in lithium-ion batteries is still somewhat different from that of the original material, indicating that the material structure may be destroyed during the lithium replenishment process and it is difficult to directly reuse it in lithium-ion batteries. Therefore, it is important to design a method for collaboratively processing retired lithium-ion battery positive electrode materials, combining the concepts of lithium-oxygen batteries and lithium-ion battery positive electrode material recycling, and establishing a complete retired positive electrode material, recycling and reuse system. Summary of the invention

[0006] The purpose of the present invention is to provide an iron phosphide active material and a preparation method and application thereof. The iron phosphide material, as a positive electrode material for a lithium oxygen battery, can provide more reactive sites for electrochemical reactions, improve material utilization, and facilitate the storage of the discharge product lithium peroxide.

[0007] To achieve the above objectives, the present invention provides a method for preparing an iron phosphide active material. Under a protective atmosphere, a retired lithium iron phosphate positive electrode material is placed above melamine, and after calcination, the iron phosphide active material is obtained.

[0008] Preferably, the calcination temperature is 650-800°C;

[0009] The calcination time is 0.5-1.5h;

[0010] The heating rate of the calcination is 5-10°C / min.

[0011] Preferably, the method specifically comprises the following steps:

[0012] (1) First, melamine is placed in an alumina crucible of a roasting device, then a gas-permeable porous material is covered on the alumina crucible, and then a retired lithium iron phosphate battery positive electrode material is placed on top of the gas-permeable porous material;

[0013] (2) After calcination under a protective atmosphere, the iron phosphide active material is obtained.

[0014] Preferably, the air-permeable porous material comprises one or more of carbon paper, carbon cloth, glass fiber and asbestos mesh;

[0015] The mass ratio of the melamine to the retired lithium iron phosphate positive electrode material is (10-15):1.

[0016] The present invention provides an iron phosphide active material prepared by the above-mentioned preparation method, including recycled retired lithium ion positive electrode materials and nitrogen-doped carbon nanotubes composited on the surface of the iron phosphide material;

[0017] The molar ratio of nitrogen to carbon is 1:(10-20).

[0018] Preferably, the nitrogen-doped carbon nanotubes have a hollow tube structure;

[0019] The length of the carbon nanotubes is 0.5-5 μm;

[0020] The diameter of the carbon nanotube is 20-80 nm;

[0021] The iron phosphide active material has a multi-level pore structure

[0022] The present invention also provides an application of an iron phosphide active material, wherein the iron phosphide active material is applied to prepare a lithium oxygen battery.

[0023] Preferably, the method comprises the following steps:

[0024] A1. Mix the iron phosphide active material, conductive carbon black and polyvinylidene fluoride in a ratio of 7:2:1, add N-methylpyrrolidone and stir to form a slurry;

[0025] A2, spray the slurry described in A1 evenly on the carbon paper with a spray gun, and dry it in a vacuum drying oven at 80° C. for 12 h;

[0026] A3, slicing the carbon paper dried in A2 to obtain an electrode sheet;

[0027] A4, select the electrode sheet in A3 as the positive electrode, metallic lithium as the negative electrode, 1M lithium trifluoromethanesulfonate as the electrolyte, tetraethylene glycol dimethyl ether as the solvent, glass fiber filter membrane as the diaphragm, and select a 2025 type perforated battery shell;

[0028] A5. Assemble the materials in A4 in the order of battery negative electrode shell, negative electrode, separator, positive electrode, nickel foam, and battery positive electrode shell, and add electrolyte dropwise to assemble a lithium oxygen battery.

[0029] Therefore, the iron phosphide active material disclosed in the present invention and its preparation method and application have the following beneficial effects:

[0030] 1. The preparation method is simple, easy to operate, and easy to achieve large-scale production;

[0031] 2. The material has a catalyst with a multi-porous structure, and is grown on the surface of an iron phosphide active material by a one-step method to obtain a lithium oxygen battery positive electrode material, namely, a nitrogen-doped carbon nanotube / iron phosphide positive electrode material;

[0032] 3. The positive electrode of lithium oxygen battery prepared by using nitrogen-doped carbon nanotubes / iron phosphide active materials has higher pore utilization and connectivity, stronger mass transfer capacity, and improved charge and discharge utilization and cycle times;

[0033] 4. As the positive electrode material of lithium oxygen battery, iron phosphide active material can provide more reactive sites for electrochemical reaction, improve material utilization, and facilitate the storage of discharge product lithium peroxide.

[0034] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a scanning electron microscope image of the iron phosphide active material in Example 1 of the present invention;

[0036] Figure 2 is a scanning electron microscope image of the comparative sample in Comparative Example 1 of the present invention;

[0037] Figure 3 4 is a discharge curve test diagram of the lithium oxygen battery in Example 4 of the present invention;

[0038] Figure 4 This is a charge and discharge overpotential test diagram of the lithium oxygen battery in Example 4 of the present invention. DETAILED DESCRIPTION

[0039] The present invention can be explained in more detail by the following examples. The purpose of disclosing the present invention is to protect all changes and improvements within the scope of the present invention. The present invention is not limited to the following examples.

[0040] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0041] The present invention has no particular limitation on the protective atmosphere, and any protective atmosphere familiar to those skilled in the art may be used. Those skilled in the art may select and adjust the protective atmosphere according to actual production conditions, raw material conditions and estimated product requirements. The protective atmosphere of the present invention is preferably nitrogen and / or an inert gas, more preferably nitrogen or argon.

[0042] The present invention has no particular limitation on the specific position of the device placed above the melamine, and those skilled in the art can select and adjust it according to the actual production situation, raw material conditions and product requirements. The device placed above the melamine in the present invention can be placed on the melamine, or can be placed above the melamine at a certain distance from the melamine. The present invention has no particular limitation on the specific value of the certain distance, and those skilled in the art can select and adjust it according to the actual production situation, raw material conditions and product requirements.

[0043] There is no particular limitation on the breathable porous material of the present invention. It can be any commonly used breathable porous material familiar to those skilled in the art. Those skilled in the art can select and adjust the breathable porous material according to the actual production situation and raw material conditions and the estimated product requirements. The breathable porous material of the present invention is preferably a high temperature resistant breathable porous material, more preferably a high temperature resistant breathable fiber material, more specifically preferably including one or more of carbon paper, carbon cloth, glass fiber and asbestos mesh, and most preferably carbon paper or carbon cloth.

[0044] The present invention has no particular limitation on the roasting equipment, and any roasting equipment familiar to those skilled in the art may be used. Those skilled in the art may select and adjust the roasting equipment according to actual production conditions, raw material conditions, and product requirements. The roasting equipment of the present invention is preferably a high-temperature tube furnace, and the crucible may specifically be an alumina crucible.

[0045] The calcination time of the present invention is not particularly limited, and the calcination temperature of such materials known to those skilled in the art can be used. Those skilled in the art can select and adjust it according to actual production conditions, raw material conditions and product requirements. The calcination time of the present invention is preferably 0.5-1.5h.

[0046] The present invention has no particular limitation on the heating rate of the calcination, and any heating rate familiar to those skilled in the art may be used. Those skilled in the art may select and adjust the heating rate according to actual production conditions, raw material conditions, and product requirements. The calcination heating rate of the present invention is preferably 5-10°C / min.

[0047] In order to improve the integrity of the overall process route, the preparation steps of the present invention may specifically be:

[0048] Step (1): weigh a certain amount of retired lithium iron phosphate positive electrode material and grind it into powder;

[0049] Step (2): weigh a certain amount of melamine solid powder and put it into an alumina crucible, cover the alumina crucible with a piece of carbon paper, place the ground lithium iron phosphate positive electrode material on the carbon paper, and put the whole into a high-temperature tube furnace;

[0050] Step (3): Using nitrogen as protective gas, start the tube furnace and heat it to the reaction temperature at a rate of 7°C / min and maintain it for several hours;

[0051] Step (4): After heating is completed, the reactants are cooled to room temperature, and the sample is taken out to obtain a positive electrode material for a lithium-oxygen battery.

[0052] In order to further illustrate the present invention, a method for preparing an iron phosphide active material and an application thereof provided by the present invention are described below in combination with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0053] Example 1

[0054] A1. Weigh 0.1 g of retired lithium iron phosphate cathode material and grind it into powder;

[0055] A2, weigh 1 gram of melamine solid powder and put it into an alumina crucible, cover the alumina crucible with a piece of carbon paper, place the ground lithium iron phosphate positive electrode material on the carbon paper, and put the whole into a high-temperature tube furnace;

[0056] A3. Using nitrogen as the protective gas, start the tube furnace and raise the temperature to 750 degrees Celsius at a rate of 7 degrees Celsius / minute, and maintain it at this temperature for 1 hour;

[0057] A4. After heating is completed, wait for the reactants to cool to room temperature, take out the sample, and obtain the iron phosphide active material.

[0058] The scanning electron microscope image of the iron phosphide active material sample obtained in this embodiment is shown in the attached specification. Figure 1 shown.

[0059] Example 2

[0060] A1. Weigh 0.1 g of retired lithium iron phosphate cathode material and grind it into powder;

[0061] A2, weigh 1 gram of melamine solid powder and put it into an alumina crucible, cover the alumina crucible with a piece of carbon paper, place the ground lithium iron phosphate positive electrode material on the carbon paper, and put the whole into a high-temperature tube furnace;

[0062] A3. Using nitrogen as the protective gas, start the tube furnace and raise the temperature to 700 degrees Celsius at a rate of 7 degrees Celsius / minute, and maintain this temperature for 1 hour;

[0063] A4. After heating is completed, wait for the reactants to cool to room temperature, take out the sample, and obtain the iron phosphide active material.

[0064] Example 3

[0065] A1. Weigh 0.1 g of retired lithium iron phosphate cathode material and grind it into powder;

[0066] A2, weigh 1 gram of melamine solid powder and put it into an alumina crucible, cover the alumina crucible with a piece of carbon paper, place the ground iron phosphide positive electrode material on the carbon paper, and put the whole into a high-temperature tube furnace;

[0067] A3, using nitrogen as protective gas, start the tube furnace and raise the temperature to 800 degrees Celsius at a rate of 7 degrees Celsius / minute, and maintain this temperature for 2 hours;

[0068] A4. After heating is completed, wait for the reactants to cool to room temperature, take out the sample, and obtain the iron phosphide active material.

[0069] Example 4

[0070] A1. The iron phosphide active material, conductive carbon black and polyvinylidene fluoride obtained in Example 1 are uniformly mixed in a ratio of 5:4:1, and N-methylpyrrolidone is added and stirred to form a slurry;

[0071] A2, spray the slurry described in A1 evenly on the carbon paper with a spray gun, and dry it in a vacuum drying oven at 80° C. for 12 h;

[0072] A3, slice the dried carbon paper in A2 using a puncher to punch out electrode sheets with a diameter of 10 mm;

[0073] A4. Select the electrode sheet in A3 as the positive electrode, 10 mm metallic lithium as the negative electrode, 1 M lithium trifluoromethanesulfonate as the electrolyte, tetraethylene glycol dimethyl ether as the solvent, glass fiber filter membrane as the diaphragm, and select a 2025 type perforated battery shell.

[0074] A5. Assemble the materials in A4 in the order of battery negative electrode shell, negative electrode, separator, positive electrode, nickel foam, and battery positive electrode shell, and add appropriate amount of electrolyte to assemble a lithium oxygen battery, and perform electrochemical test on the lithium oxygen battery.

[0075] like Figure 3 As shown, when the current density is 200mA / g, the initial specific capacity of the lithium-oxygen battery is 6721mAh / g.

[0076] like Figure 4 As shown in the figure, when the current density is 200mA / g and the limited capacity is 500mAh, the first-circuit overpotential reaches 1.47V.

[0077] It is shown that the iron phosphide active material prepared by the present invention can be used as the positive electrode of the lithium oxygen battery, which can effectively improve the charge and discharge utilization rate and cycle times of the battery; and is beneficial to the storage of the discharge product lithium peroxide.

[0078] Comparative Example 1

[0079] A1. Weigh 0.1 g of retired lithium iron phosphate cathode material and grind it into powder;

[0080] A2, weigh 1 gram of melamine solid powder and put it into an alumina crucible, cover the alumina crucible with a piece of carbon paper, place the ground iron phosphide positive electrode material on the carbon paper, and put the whole into a high-temperature tube furnace;

[0081] A3. Using nitrogen as protective gas, start the tube furnace and raise the temperature to 650 degrees Celsius at a rate of 7 degrees Celsius / minute, and maintain this temperature for 2 hours;

[0082] A4. After heating is completed, wait for the reactants to cool to room temperature, take out the sample, and obtain a comparative sample.

[0083] The scanning electron microscope image of the iron phosphide active material sample obtained in this comparative example is shown in the attached specification. Figure 2 As shown in the instruction manual. Figure 1 With the instruction manual Figure 2 In comparison, it is known that the material prepared in Example 1 has a multi-porous structure grown on the surface of the iron phosphide active material.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an iron phosphide active material, characterized in that: Under a protective atmosphere, a retired lithium iron phosphate positive electrode material is placed on top of melamine, and after calcination, an iron phosphide active material is obtained; the iron phosphide active material is nitrogen-doped carbon nanotubes composited on the surface of the iron phosphide material; The specific steps include: (1) First, melamine is placed in an alumina crucible of a roasting device, then a gas-permeable porous material is covered on the alumina crucible, and then a retired lithium iron phosphate battery positive electrode material is placed on top of the gas-permeable porous material; (2) After calcination under a protective atmosphere, an iron phosphide active material is obtained; the calcination temperature is 700-800°C.

2. The method for preparing an iron phosphide active material according to claim 1, characterized in that: The calcination time is 0.5-1.5 h; The heating rate of the calcination is 5-10°C / min.

3. The method for preparing an iron phosphide active material according to claim 1, characterized in that: The air-permeable porous material includes one or more of carbon paper, carbon cloth, glass fiber and asbestos mesh; The mass ratio of the melamine to the retired lithium iron phosphate positive electrode material is (10-15):

1.

4. An iron phosphide active material prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The iron phosphide active material is nitrogen-doped carbon nanotubes composited on the surface of the iron phosphide material; The molar ratio of nitrogen to carbon is 1:(10-20).

5. An iron phosphide active material according to claim 4, characterized in that: The nitrogen-doped carbon nanotubes have a hollow tube structure; The length of the carbon nanotubes is 0.5-5 μm; The diameter of the carbon nanotube is 20-80 nm; The iron phosphide active material has a multi-level pore structure.

6. Use of the iron phosphide active material according to any one of claims 4 to 5, characterized in that: The iron phosphide active material is used for preparing lithium oxygen batteries.

7. The use of an iron phosphide active material according to claim 6, characterized in that: The following steps are involved: A1. Evenly mix the iron phosphide active material, conductive carbon black and polyvinylidene fluoride in a ratio of 7:2:1, add N-methylpyrrolidone and stir to form a slurry; A2, spray the slurry described in A1 evenly on the carbon paper with a spray gun, and dry it in a vacuum drying oven at 80° C. for 12 h; A3, slicing the carbon paper dried in A2 to obtain an electrode sheet; A4, select the electrode sheet in A3 as the positive electrode, metallic lithium as the negative electrode, 1M lithium trifluoromethanesulfonate as the electrolyte, tetraethylene glycol dimethyl ether as the solvent, glass fiber filter membrane as the diaphragm, and select a 2025 type perforated battery shell; A5. Assemble the materials in A4 in the order of battery negative electrode shell, negative electrode, separator, positive electrode, nickel foam, and battery positive electrode shell, and add electrolyte dropwise to assemble a lithium oxygen battery.

Citation Information

Patent Citations

  • Method for preparing iron phosphide and carbon composite structure by utilizing carbothermic reaction

    CN104084224A

  • Lithium-oxygen secondary battery cathode and preparation method thereof, lithium-oxygen secondary battery

    CN106953101A

  • Method for efficiently converting waste lithium battery into porous carbon-based phosphide composite material and energy storage application

    CN115911634A